Given `cos(120+45)`
`cos(u+v)=cos(u)cos(v)-sin(u)sin(v)`
`cos(120+45)=cos(120)cos(45)-sin(120)sin(45)`
`cos(120+45)=(-1/2)(sqrt2/2)-(sqrt3/2)(sqrt2/2)=-sqrt2/4-sqrt6/4=(-sqrt2-sqrt6)/4`
Given `cos(120)+cos(45)`
`cos(120)+cos(45)=(-1/2)+sqrt2/2=(-1+sqrt2)/2`
``
``
` `
Given `cos(120+45)`
`cos(u+v)=cos(u)cos(v)-sin(u)sin(v)`
`cos(120+45)=cos(120)cos(45)-sin(120)sin(45)`
`cos(120+45)=(-1/2)(sqrt2/2)-(sqrt3/2)(sqrt2/2)=-sqrt2/4-sqrt6/4=(-sqrt2-sqrt6)/4`
Given `cos(120)+cos(45)`
`cos(120)+cos(45)=(-1/2)+sqrt2/2=(-1+sqrt2)/2`
``
``
` `
No comments:
Post a Comment